Dielectric properties of onion‐like carbon and detonation nanodiamond/polydimethysiloxane composites. Issue 11 (1st July 2014) - Macutkevic, Jan; Banys, Juras; Moseenkov, Sergey; Kuznetsov, Vladimir; Nunn, Nicholas; Shenderova, Olga
<x xml:space="preserve">Abstract</x> Results of dielectric investigations of onion‐like carbon (OLC) and detonation nanodiamond (DND)/polydimethysiloxane composites in wide frequency (20 Hz–3 THz) and temperatures (26–300 K) ranges are presented. The percolation threshold in OLC composites is 6.8 vol%. Electrical conduction in the OLC composites above the percolation threshold occurs mainly due to electron tunneling between OLC clusters and quasi‐one‐dimensional hopping inside the clusters. Hopping almost vanishes at frequencies above 100 GHz, where phonon contribution to the dielectric permittivity dominates. At low concentrations of nanocarbon particles (concentrations below the percolation threshold for OLC), the dielectric properties of the OLC and DND composites are similar. However, DNDs provide a noticeable improvement of the mechanical properties of the composites, in contrast with OLC. Therefore, a combination of the two nanomaterials in the composites could be beneficial. POLYM. COMPOS., 36:2084–2092, 2015. © 2014 Society of Plastics Engineer